Directions of automatization for calculation of soil qualitative assessment - Cherlinka, V.R.; Zaharovskyy , V.S. (AgroChemistry and Soil Science, 2016)
It was considered results of calculations of agrochemical and environmental-agrochemical scores by the standard procedure and several alternative indicators. It was proposed to perform calculations by means of Calculator of Quality of Soils of Ukraine. Use of this calculator allowed to reveal potential ways to improve its performance. Since the distribution of soil properties have a continual character, it makes sense to count and corresponding continual agrochemical and ecological-agrochemical points. The implementation of this approach is possible with the use of modern GIS tools. Currently we are working on the implementation of the described calculations to free GIS GRASS, which is distributed under the GNU GPL General Public License and is a powerful tool for the implementation of the conceived project. This interface will be written in the programming language Pyton, mapping aspects will be implemented by means of elements of map algebra. We feel that this approach would have clear advantages in today's precision agriculture and soil monitoring.